STRESS REGIME ANALYSIS IN THE STRUCTURAL TRANSTITION BETWEEN SUMATRA AND JAWA - Hikhmadhan Gultaf; Benyamin Sapiie; Wahyu Triyoso; Meli Hadiana; Yehezkiel Halauwet; Herlina Almanda Anna Maria Narwadan (Testing Center for Oil and Gas LEMIGAS, 2025)
The structural transition between Sumatra and Java presents significant geological challenges due to the change in the orientation of the convergent plate boundary, shifting from NW-SE in western Sumatra to W-E in southern Java. This study focuses on the regions of Lampung (representing Sumatra's tectonics), West Java (representing Java's tectonics), and the Sunda Strait as the boundary between them. The research aims to map tectonic stress conditions using formal stress inversion methods based on earthquake focal mechanism data, constrained to depth intervals of 0-15 km and 15-33 km. Focal mechanism data are categorized by geographic and regional structural geology with kinematic homogeneity, leading to the identification of ten inversion zones. Findings show that Lampung's average stress regime ( ) is strike-slip fault regime at both depth intervals. The Sunda Strait displays a transtensive fault regime across these depths, while West Java has a thrust fault regime at 0-15 km, transitioning to strike-slip fault regime at 15-33 km.